Comparison of the Mitophagy and Apoptosis Related Gene Expressions in Waste Embryo Culture Medium of Female Infertility Types - Duygu Kütük; Çağrı Öner; Murat Başar; Berkay Akcay; İbrahim Orçun Olcay; Ertuğrul Çolak; Belgin Selam; Mehmet Cincik (Life)
Mitochondria is an important organelle for the oocyte-to-embryo transition in the early embryonic development period. The oocyte uses mitochondria functionally and its mitochondrial DNA (mtDNA) content as the main energy source in the embryo development at the preimplantation stage. The aim of this study is to compare mitophagic, apoptotic and humanin gene expressions from the culture medium fluid in which embryos are developed and monitored among normoresponder (NOR), polycystic ovary syndrome (PCOS), young and older patients with poor ovarian reserve (POR). The study groups consisted of infertile patients who applied to the Bahçeci Umut IVF Center as NOR (Control), PCOS, POR-Advanced (POR-A) and POR-Young (POR-Y). After the isolation of total RNA from the collected samples, MFN1, MFN2, PINK1, PARKIN, SMN1, SMN2, p53 and Humanin gene expressions were determined by Real Time-PCR. The average age of only the POR-A was determined to be higher than the NOR (p < 0.001). The MFN1, SMN2 (p < 0.05), Humanin and p53 gene expressions (p < 0.001) increased, while PINK1 gene expression decreased (p < 0.05), in the POR-Y compared to the NOR. A decrease in MFN2, PARKIN (p < 0.05) and PINK1 gene expressions was determined in the PCOS compared to the NOR (p < 0.001). Furthermore, a decrease was observed in MFN2, PINK1 (p < 0.001) and Humanin gene expressions compared to the NOR (p < 0.05). The current data are the first in the literature determining the apoptotic and mitophagic status of the oocyte. The current results prove that waste embryo culture fluid may provide a non-invasive profile for important cellular parameters such as mitochondrial dysfunction in female infertility. The evaluation of significant cellular parameters can be performed much earlier without any intervention into the embryo.